Improved soil characteristics in the deeper plough layer can increase grain yield of winter wheat - Jin CHEN; Dang-wei PANG; Min JIN; Yong-li LUO; Hao-yu LI; Yong LI; Zhen-lin WANG (Journal of Integrative Agriculture)
In the North China Plain (NCP), soil deterioration threatens winter wheat (Triticum aestivum L.) production. Although rotary tillage or plowing tillage are two methods commonly used in this region, research characterizing the effects of mixed tillage on soil characteristics and wheat yield has been limited. A fixed-site field trial was carried out during 2011–2016 to examine the impacts of three tillage practices (5-year rotary tillage with maize straw removal (RT); 5-year rotary tillage with maize straw return (RS); and annual RS and with a deep plowing interval of 2 years (RS/DS)) on soil characteristics and root distribution in the plough layer. Straw return significantly decreased soil bulk density, increased soil organic carbon (SOC) storage and SOC content, macro-aggregate proportion (R0.25) and its stability in the plough layer. The RS/DS treatment significantly increased the SOC content, total nitrogen (TN), and root length density (RLD) in the 10–40 cm layer, and enhanced the proportion of RLD in the 20–30 and 30–40 cm layers. In the 20–30 and 30–40 cm layers, an increase in SOC and TN could lead to higher grain production than commensurate increases in the surface layer, resulting in a sustainable increase in grain yield from the RS/DS treatment. Thus, the RS/DS treatment could lead to high productivity of winter wheat by improving soil characteristics and root distribution at the deeper plough layer in the NCP.